Evaluation of surface roughness of restorative dental composites: influence of depth cure, time and storage medium (Research, Society and Development, 2021)
Bulk-Fill resin composites have gained popularity because their incremental insertion of up to 5.0 mm thickness, achieved through the composition, allowing an adequate degree of conversion. The reduced degree of conversion may alter the properties of dental composites as well as surface roughness. To evaluate the influence of polymerization depth, time and storage media on the hydrolytic degradation of restorative dental composites using surface roughness test. Twenty specimens were prepared for each material (Filtek Z250 XT, Filtek Bulk Fill e Tetric N-Ceram Bulk Fill) using two matrices with a central cavity of 5.0 mm in diameter and a thickness of 2.0 mm. 10 p.s. for each immersion medium (water and ethanol 75%) and depth of polymerization of 2.0 and 4.0 mm, for evaluation of surface roughness. After each storage period (24 hours, 90 days and 180 days) the surface roughness analysis was performed in Profilometer. After 24 hours and 90 days of storage, Filtek Z250 showed increased roughness with increasing polymerization depth. Filtek Bulk Fill showed significantly higher surface roughness when compared to Tetric N-Ceram Bulk Fill in all storage periods and immersion media. After 180 days, there was an increase of roughness for all materials, depths and storage medium evaluated. All materials show an increase in the surface roughness over time, probably due to hydrolytic degradation.